Peran Guru Private Dalam Meningkatkan Motivasi Belajar Siswa di Masa Pandemi Covid 19 Desa Paya Perupuk Kecamatan Tanjung Pura Kabupaten Langkat - Muhammad Solihin Pranoto; Sejayanti Sejayanti; Devi Kumala Sari; Minto Haribowo (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
The role of private teachers can be a place to mprove the quality and achievement of students. The teacher is seen as a person who is responsible for the success or failure of learning activities for each individual change, both in terms of providing motivation, forstering moral values and also as a controller for each student. The purpose of this study is to determine the role of private teachers in increasing learning motivation in pandemic covid 19 paya perupuk village, Tanjung Pura district, Langkat Regency. The research method with an approach in conducting research that is oriented toward fenomena, observation, interview and study documentation. This research shows that in general it can be described that the role of a new private teacher is created by involving various parties internal and external and applying systematic and appropriate steps. With private lessons, it provides convenience and helps children in the village of Paya Perupuk in overcoming learning problems that they consider difficult. The problems faced by every child in Paya Perupuk Village will be solved by private tutors, making it easier to understand lessons.